The practice of social research - Babbie, Earl R. (Wadsworth Cengage Learning, 2013)
A guide to research as practiced by social scientists. It gives you the tools you need to apply research concepts practically, as both a researcher and a consumer. It emphasizes the process by showing you how to design and construct projects, introducing the various observation modes in use, and answering critical questions about research methods